2006
DOI: 10.1002/cncr.22385
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors and outcome of recurrence in childhood acute myeloid leukemia

Abstract: Dixon imaging techniques derive chemical shift‐separated water and fat images, enabling the quantification of fat content and forming an alternative to fat suppression. Whole‐body Dixon imaging is of interest in studies of obesity and the metabolic syndrome, and possibly in oncology. A three‐point Dixon method is proposed where two solutions are found analytically in each voxel. The true solution is identified by a multiseed three‐dimensional region‐growing scheme with a dynamic path, allowing confident region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
92
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(109 citation statements)
references
References 57 publications
12
92
1
2
Order By: Relevance
“…3 Data from the St Jude institutional trials showed a 5-year OS of 23% in 160 relapse patients. 4 Within the AML-BFM study periods (Figure 1), CR and survival rates after first relapse improved despite the intensification of first-line induction therapy. This improvement could not be related to the type or the intensity of relapse chemotherapy, which might result from the heterogeneity of relapse treatment and the low numbers of patients treated according to the different regimens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Data from the St Jude institutional trials showed a 5-year OS of 23% in 160 relapse patients. 4 Within the AML-BFM study periods (Figure 1), CR and survival rates after first relapse improved despite the intensification of first-line induction therapy. This improvement could not be related to the type or the intensity of relapse chemotherapy, which might result from the heterogeneity of relapse treatment and the low numbers of patients treated according to the different regimens.…”
Section: Discussionmentioning
confidence: 99%
“…5 French-American-British (FAB) subtypes as well as cytogenetics and intensity of first-line treatment including allogeneic stem cell transplantation (allo-SCT) are well recognized as additional prognostic factors in the relapse setting. 4,7,8 Allo-SCT in CR2 has been associated with a 5-year OS rate of 62% in recent studies. 9 From 1987 to 2003, a total of 1251 patients with de novo AML were registered in three consecutive protocols of the AML-Berlin/Frankfurt/Muenster study group (AML-BFM-87, AML-BFM-93, AML-BFM-98), of whom 379 patients relapsed between 1987 and 2007. In this study, we analyze the outcome after relapse in this cohort on the basis of the intensity of firstline treatment, including allo-SCT or autologous SCT (auto-SCT), duration of first remission, modalities of relapse treatment and achievement of a second complete remission (CR2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,24 The median age of our series of children was just over 2 years. It could be argued that young age may have influenced the good outcome in our patient group, although very recent data from CIBMTR have suggested an increased risk of relapse in children under 5 years of age (Davies SM, personal communication).…”
Section: Discussionmentioning
confidence: 91%
“…However, those that relapse within 1 year from the time of diagnosis have a poorer prognosis. 3,4 Children who are refractory to de novo or salvage chemotherapy have a dismal prognosis with less than 20% of children being salvaged by SCT. 5 A poor prognosis has also been associated with secondary AML: 15% at 3 years.…”
Section: Introductionmentioning
confidence: 99%